Fabrication and microstructural analysis of CNTs reinforced copper matrix nanocomposites via MIM technique - Muhsan, A.S. (2013)
Carbon nanotubes (CNTs) reinforced copper (Cu) matrix nanocomposites prepared via advanced fabrication method is presented. Functionalization and ultrasonication processes have been applied to enhance the dispersion of purified CNTs and creates sidewalls groups that have the potential to bond CNTs to the metal matrix. The main part of this approach was metal injection molding (MIM) technique, which is a combination of powder metallurgy and plastic injection molding technique. Preparation of MIM feedstock required a melting and mixing process of binder system (polymers) with the solid loading, which has been carried out using a twin screw rotor machine. This machine provides a viscous media of the molten binder with high shear forces that allow the additives (carbon nanotubes/copper powder) to be mixed properly and exfoliate the CNTs clusters with uniformdispersion inside the Cu matrix. Subsequently, to prove our expected results, observation tests of TEM, SEM, FESEM and CNTS were employed and discussed literally. Â© (2014) Trans Tech Publications, Switzerland.